DEVELOPMENT OF A LEARNING MEDIUM BASED ON EFAS TRADITIONAL GAME (ENGKLEK FUN AND SMART) TO IMPROVE STUDENTS' COMMUNICATION ABILITY IN THEMATIC LEARNING - Zhao, Bin; Anas, Nirwana (UIN Sunan Kalijaga Yogyakarta, 2023)
Traditional games must be adapted for the present since they have cultural values that need to be conserved for future generations. This study attempts to create an EFAS (Engklek Fun and Smart) medium version of a typical game product. With research experience at IES Al-Ittihadiyah Berastagi, this study applies the Research and Development (R&D) technique. Forty-five first graders of Islamic Elementary School (IES) Al-Ittihadiyah Berastagi became the study participants. The findings indicate that the EFAS medium is recognized as valid. The